Pengetahuan dan Perilaku Remaja Putri tentang Pencegahan Kanker Serviks yang Diberikan Komunikasi, Informasi, dan Edukasi melalui Media Sosial Whatsapp - I Gusti Agung Manik Karuniadi; Luh Putu Widiastini (Poltekkes Kemenkes Maluku, 2020)
The proportion of women under 35 who suffer from cervical cancer increases from 9% to 25%. The risk of cervical cancer is important to be known by every woman early on, especially those who have experienced menstruation, namely in the teenage phase. This study aims to determine the effect of communication, information, and education through Whatsapp social media on the knowledge and behavior of young women about cervical cancer. Pre-experimental research design with one group pre-test and post-test design. The study was conducted on 40 midwifery students of STIKES Bina Usada Bali with a total sampling technique in May to July 2019. The results of this study found that there was no effect of providing communication, information, and education through Whatsapp on the knowledge of young women. This can be seen from the results of statistical tests conducted p-values obtained 0.768, but has a significant effect on the behavior of adolescent girls, indicated by the results of p-value 0.044 (p<0.05). The results of this study get the results that there is an influence of provision of communication, information, and education through Whatsapp social media on teenage girl behavior about cervical cancer.